2004
DOI: 10.1111/j.1538-7836.2004.00896.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluvastatin inhibits up‐regulation of tissue factor expression by antiphospholipid antibodies on endothelial cells

Abstract: Summary. Background: Mechanisms of thrombosis induced by antiphospholipid (aPL) antibodies include up-regulation of tissue factor (TF) expression on endothelial cells (ECs). Statins have been shown to reduce levels of TF induced by tumor necrosis factor (TNF-a) and lipopolysaccharide (LPS) on ECs. In a recent study, fluvastatin inhibited thrombogenic and proinflammatory properties of aPL antibodies in in vivo models. The aim of this study was to determine whether fluvastatin has an effect on aPL-induced expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
75
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(81 citation statements)
references
References 62 publications
4
75
0
2
Order By: Relevance
“…It is surprising that none of the IS4 variants enhanced expression of tissue factor on the cultured HUVECs because numerous previous studies have demonstrated aPL mediated up-regulation of tissue factor from HUVECs (15,16,41). Furthermore, enhanced tissue factor expression is thought to be a major mechanism of thrombosis in patients with APS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is surprising that none of the IS4 variants enhanced expression of tissue factor on the cultured HUVECs because numerous previous studies have demonstrated aPL mediated up-regulation of tissue factor from HUVECs (15,16,41). Furthermore, enhanced tissue factor expression is thought to be a major mechanism of thrombosis in patients with APS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown aPL to activate cultured HUVECs leading to up-regulation of E-selectin, ICAM-1, VCAM-1, and tissue factor (15,16). Using in vivo models of microcirculation, aPL have been shown to increase leukocyte adherence to EC and enhance thrombus formation (17).…”
mentioning
confidence: 99%
“…In separate studies, fluvastatin has been shown to decrease leukocyte-endothelial adhesion in postcapillary venules (135). Fluvastatin also significantly decreases expression of tissue factor by HUVECs exposed to human antiphospholipid antibodies (136).…”
Section: Abeles and Pillingermentioning
confidence: 95%
“…Additionally, several classical drugs, such as statins and hydroxychloroquine, can have antithrombotic effects through these mechanisms of action [13,14].…”
Section: Plateletsmentioning
confidence: 99%